Induksi Mutasi Tanaman Leunca (Solanum nigrum L.) untuk Meningkatkan Keragaman Kandungan Tanin - Saragih, Siti Hartati Yusida; Aisyah, Syarifah Iis; Sobir, dan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
Leunca (Solanum nigrum L. ) is one of the indigenous vegetables in Indonesia. The fruit of this vegetable is green and has bitter taste because of its tannin content. The objectives of this study were to get lethal dose 50 (LD50), diversity and to obtain candidates of mutant plants with high and low tannin content in young fruit and ripe fruit in leunca. The research was conducted at Pasir Kuda experimental station, Bogor; National Nuclear Energy Agency (BATAN), Jakarta; and postharvest laboratory of the Center for Tropical Horticulture Studies (PKHT IPB), Bogor, from December 2016 to July 2017. Leunca accession of SN 20 and SN 29 were irradiated using doses of 0, 100, 150, 200, and 250 Gy of gamma ray. The LD50 values for SN 20 and SN 29 were 171.944 Gy and 190.949 Gy, respectively. The analysis of tannin content was performed based on permanganate method by titration using potassium permanganate. The results showed that the highest tannin content of green stage fruit was found in SN20D3.5 with 200 Gy dose and the lowest was found in SN29D1.5 with 100 Gy dose. The highest tannin content of ripe fruit was found in SN20D4.6 with dose of 250 Gy and the lowest was found in SN20D3.1 with dose of 200 Gy. Recommended tannin content for leunca is the low tannin content.Keywords: diversity, gamma ray, indigenous vegetable, irradiation, LD50